Instrumen Penentuan Kebutuhan Pelatihan dalam Penyuluhan Sosial - Mokhamad O Royani; Amri Jahi; Darwis S. Gani; Djoko Susanto; Gusti Putu Purnaba (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2010)
The information about training needs for the social service employee toward social extension recently has not been available; therefor it is important to design a training in order to realize the competence of social extension. Lacking of those information due to the fact that there is not a valid dan reliable instrument to collect data on training needs of the social extension. The objective of this research is to determine a valid and reliable instrument to measure training needs on social extension. The research was carried out in October to November 2008 at eleven regencies/cities at south Kalimantan. The total of sample 228 people, taken randomly from the population of social service employee in south Kalimantan. The result of research is four kinds of instrument which is used in this research valid and reliable to measure the traning needs on social extension. The suggestion is the decision to choose instrument which relatively the same about the level of validity and its reliability on the basis of dimension consideration to the training needs that want to know.Key words: training needs, social extension, instrument of training needs assesment